Urbanization and environmental disruption of catchment basins as a result of housing development at Cidade Operária and adjacencies, Maranhão Island - Sousa, Izis Deise Silva de; Veloso, Geiza Paula de Sousa; Dias, Luiz Jorge Bezerra da Silva (Sociedade & Natureza, 2005)
The Industrial Revolution was followed by an increase in the rates of urbanization, particularly after the second-half of the 20th century. In this context, Sao Luis, the capital city of Maranhao State, adopted a housing development policy that was aimed at reducing the housing deficit in the municipality. The construction of the Cidade Operaria housing complex was a response to these explicit social needs, which have intensified since the 1970s. The occupation of the complex, however, resulted in considerable damage to the ecological integrity of the adjacent habitats. The complex is located in the catchment basin of the Paciencia and Santo Antonio rivers, at the center of the Maranhao Island. This study analyzes the spatial and temporal dynamics of the area's urbanization process, which occurred in three phases: the period between 1976 and 1981 saw the removal of the original vegetation cover in some areas, as a result of the first settlement in Parque Zelandia. During that period, subsistence agriculture was common practice along the margins of streams and rivers. The second phase corresponds to the construction of the Cidade Operaria housing complex, which occurred between 1981 and 1988. During that time, 860 ha of land were cleared and urbanized, resulting in considerable environmental damage. Changes of relief, due to grading and earthmoving activities, lead to irreversible modifications in the course of rivers and streams; many tributaries of the rivers Paciencia and Santo Antonio had theirs springs smothered by earthfills; construction of houses and the use of asphalt on roads reduced soil permeability, increasing the depth of the water table; the release of untreated sewage contaminated the drainage basins. During the third phase, which started in 1988, the environmental degradation was intensified by the occupation of areas adjacent to the housin complex. This model of urbanization has caused irreversible damage to the hydrology and water quality in the study area, and this article aims to provide an incentive for the creation of land-use planning and management strategies that include protective and restorative measures to reduce degradation of catchment basins as a result of urbanization